Neolignans from leaves of Miliusa mollis - Sawasdee,K. (Elsevier, 2015)
From the leaves of Miliusa mollis Pierre (Annonaceae), five new dihydrobenzofuran neolignans, namely miliumollin, 7-methoxymiliumollin, 3′-methoxymiliumollin, 4′-O-methylmiliumollin and miliumollinone, and a new 8-O-4′ neolignan named miliusamollin were isolated, and their structures were elucidated through analysis of spectroscopic data. Miliumollin, 3′-methoxymiliumollin, miliumollinone and decurrenal exhibited weak cytotoxicity against KB, MCF7 and NCI-H187 cells. Miliumollinone possessed weak inhibitory effects against herpes simplex virus types 1 and 2. None of the isolates displayed inhibitory activity against avian influenza H5N1 neuraminidase. © 2013 Elsevier B.V.